Kajian Etnomatematika Pada Maha Vihara Maitreya Kompleks Perumahan Cemara Asri - Utami Hasibuan, Mega; Firia, Nabila; Mahfuzah Hrp, Marwah; Hidayati, Nadia; Rachma, Dianny; Humayra, Lutfia; Andhany, Ella (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research examines the application of ethnomathematics to the architecture of the Maha Vihara Maitreya Complex Cemara Medan with a focus on mathematical elements such as geometric shapes, symmetry patterns and building proportions. Using a qualitative descriptive approach, data collection was carried out through direct observation and document study. The research results show that the temple design, including triangular roofs, octagonal windows, fractal ornaments, and tubular columns, reflects the integration of mathematics and Buddhist culture. These elements not only beautify the building but also function as a contextual source of mathematics learning. This research highlights the importance of linking mathematics education with cultural values ​​to increase understanding and preservation of local traditions.